2021
DOI: 10.34142/hsr.2021.07.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fighting styles of qualified veteran boxers based on cluster analysis of biomechanical and psychophysiological indicators

Abstract: Purpose: to reveal the styles of fighting veteran boxers on the basis of a multivariate analysis of psychophysiological and biomechanical indicators. Material and methods. The study involved 42 qualified veteran boxers (age 45-50 years). As research methods, we used a biomechanical analysis of the indicators of the speed of movement of various points and the values ​​of the angles in the joints when performing a direct blow by boxers. The psychophysiological method was used to determine the time of a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This study confirmed the results of our previous studies [26,33] on the informativeness of psychophysiological and biomechanical indicators to determine the propensity to a certain style of fighting in boxing. Confirmation of this position is due to the results of a comparative analysis of groups of athletes tested for psychophysiological and biomechanical indicators.…”
Section: Discussionsupporting
confidence: 90%
“…This study confirmed the results of our previous studies [26,33] on the informativeness of psychophysiological and biomechanical indicators to determine the propensity to a certain style of fighting in boxing. Confirmation of this position is due to the results of a comparative analysis of groups of athletes tested for psychophysiological and biomechanical indicators.…”
Section: Discussionsupporting
confidence: 90%
“…From the data obtained, it follows that the work of the nervous system has the same regularities as the work of the muscular apparatus. This is not accidental, since the muscular work characteristic of any movement is guided by the nervous system [37][38][39]. And therefore, the properties of the nervous system also affect the speed and accuracy of movements over time.…”
Section: Resultsmentioning
confidence: 99%
“…The set goal assumed that the determination of the individual factor structure of the complex readiness of veteran boxers on the basis of psychophysiological and biomechanical indicators will make it possible to determine the hidden relationships between a wide range of psychophysiological and biomechanical indicators, combining the analyzed indicators into groups (factors) and determine the individual severity of each factor in each athlete ... After analyzing the individual severity of each factor for each athlete, we identified 3 groups of athletes: group 1 -the severity of the factor "Speed and coordination endurance" prevails (more than 80% of the maximum value) and insignificant (less than 30% of the maximum) severity of the factor " Speed". This means that these athletes are distinguished by their ability to maintain high speed and accuracy (coordination) of actions for a long time [37][38][39]. That is why we named this group "Speed and coordination endurance".…”
Section: Explained Total Variance In Factor Analysis Of Biomechanical...mentioning
confidence: 99%
“…There are three options for tactical styles of fighting in martial arts: game, power, tempo 6 . Kozin et al 7 proposed psychophysiological and biomechanical research methods that reveal boxers' predispositions to a certain fighting style. “Psychophysiological features of boxers of different styles of fighting are reflected in the features of the technique of a direct blow.…”
Section: Introductionmentioning
confidence: 99%